Helicobacter pylori infection recurrence in developed versus developing countries – a systematic review and meta-analysis - M. Schechter; Y. Niv (Microbiota in Health and Disease)
Objective: Half of the world’s population is infected with Helicobacter pylori (H. pylori), which can cause gastric diseases and must be eradicated. The reinfection rate, the colonization rate with a new strain usually after more than 12 months of successful eradication, is considered higher in developing countries than developed countries due to lower investment in sanitation and hygiene or a higher population density. The study aimed to analyze and understand H. pylori recurrence rates in developed and developing countries and compare the results from 2013 to 2023 to those between 1992 and 2006.